2017
DOI: 10.1016/j.cognition.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Auditory processing deficits are sometimes necessary and sometimes sufficient for language difficulties in children: Evidence from mild to moderate sensorineural hearing loss

Abstract: There is a general consensus that many children and adults with dyslexia and/or specific language impairment display deficits in auditory processing. However, how these deficits are related to developmental disorders of language is uncertain, and at least four categories of model have been proposed: single distal cause models, risk factor models, association models, and consequence models. This study used children with mild to moderate sensorineural hearing loss (MMHL) to investigate the link between auditory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 76 publications
0
46
0
Order By: Relevance
“…Auditory processing has frequently been investigated in dyslexia, and empirical evidence, often-though not always-has confirmed the presence of an auditory deficit, especially when stimuli contain acoustic changes over time (Hämäläinen, Salminen, & Leppänen, 2012). The observed auditory impairments can hinder phoneme perception (Talcott et al, 2002;Vandermosten et al, 2010Vandermosten et al, , 2011 but can also affect other aspects of speech processing such as syllable identification and the processing of prosody (Goswami, 2015;Halliday, Tuomainen, & Rosen, 2017;Law et al, 2017;Poelmans et al, 2011). Moreover, auditory deficits can only partially explain the variability seen in dyslexics' phonological and reading performance (Law et al, 2017); hence, deficient statistical learning might also contribute.…”
Section: Introductionmentioning
confidence: 99%
“…Auditory processing has frequently been investigated in dyslexia, and empirical evidence, often-though not always-has confirmed the presence of an auditory deficit, especially when stimuli contain acoustic changes over time (Hämäläinen, Salminen, & Leppänen, 2012). The observed auditory impairments can hinder phoneme perception (Talcott et al, 2002;Vandermosten et al, 2010Vandermosten et al, , 2011 but can also affect other aspects of speech processing such as syllable identification and the processing of prosody (Goswami, 2015;Halliday, Tuomainen, & Rosen, 2017;Law et al, 2017;Poelmans et al, 2011). Moreover, auditory deficits can only partially explain the variability seen in dyslexics' phonological and reading performance (Law et al, 2017); hence, deficient statistical learning might also contribute.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of phonological skills and their role in learning to read found that phonemic awareness had the strongest correlation with word reading ability (Melby-Lervåg et al, 2012). However, there is much debate over what timescale these phonological deficits are related to (Hämäläinen et al, 2012;Halliday et al, 2017). Currently, the two most popular theories for phonological deficits in dyslexia are the rate-processing constraint hypothesis, which relates to short timescale processing (Tallal, 1980;1984;2004; see also Farmer and Klein, 1995, for a review), and the temporal sampling framework hypothesis (Goswami, 2011), which relates to longer timescale processing.…”
mentioning
confidence: 99%
“…Gamma neural oscillations predominantly in the left auditory cortex are believed to correspond to phonemic-level processing (Poeppel, 2003;Giraud and Poeppel, 2012). A rate-processing deficit is thought to lead to inaccurate phoneme perception and, therefore, result in the development of less precise phonological representations of these phonemes (see Halliday et al, 2017;Hämäläinen et al, 2012, for a review).…”
mentioning
confidence: 99%
See 2 more Smart Citations